Analisis Faktor-Faktor Yang Mempengaruhi Audit Report Lag Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Mugi Handayani; Rina Trisnawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to analyze the influence of Audit Tenure, Audit Committee Size, Audit Committee Expertise, Audit Committee Meetings and Financial Distress on Audit Report Lag. The population in this research is manufacturing companies in the goods and consumption sector listed on the Indonesia Stock Exchange in 2019-2022, totaling 78 companies. The sample was determined using a purposive sampling technique, namely selecting samples based on certain criteria, so that 140 samples were obtained. Data processing in this study used the Statistical Package For The Social Sciences (SPSS) software version 25, showing that audit committee meetings and financial distress had an effect on audit report lag in goods and consumer sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. , while audit tenure, audit committee size and audit committee expertise have no effect on audit report lag in consumer goods and manufacturing sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period.